التعلق بالأقران وعلاقته بالتعاطف الوجداني - شحاده, أنس محمد; العاسمي, رياض (جامعة الوادي University of Eloued, 2016)
يهدف هذا البحث إلى الكشف عن العلاقة المحتملة بين التعلق بالأقران والتعاطف الوجداني لدى عينة من طلبة الماجستير في كلية التربية بجامعة دمشق، وقد حاول البحث الإجابة عن التساؤلات التالية: هل هناك علاقة بين التعلق بالأقران والتعاطف الوجداني لدى طلبة الماجستير في كلية التربية بجامعة دمشق؟ وهل هناك فروق بين طلبة الماجستير في درجة التعلق بالأقران والتعاطف الوجداني تعزى لمتغير التخصص الدراسي؟ وقد تم استخدام مقياس التعلق بالأقران ومقياس التعاطف الوجداني للإجابة عن فرضيات البحث؛ وقد توصل البحث إلى مجموعة من النتائج أبرزها ما يلي: وجود علاقة ارتباط إيجابية بين التعلق بالأقران والتعاطف الوجداني لدى عينة البحث، وعدم وجود فروق بين طلبة الماجستير في درجة التعلق بالأقران، في حين وجدت فروق بين طلبة الماجستير في درجة التعاطف الوجداني وكانت الفروق لصالح التخصصات النفسية، ووجود أثر للتفاعل بين التعلق بالأقران والتعاطف الوجداني لدى عينة البحث إذ كان حجم الأثر كبيراً. This research aims to detect possible relationship between attachment to peers and emotional empathy among a sample of the master's students in the College of Education, University of Damascus. The research attempted to answer the following questions: Is there a relationship between the attachment to peers and emotional empathy among the master's students in the College of Education at the University of Damascus? Are there differences between master's students in the degree of attachment to peers and emotional empathy due to academic discipline? The researcher used the attachment to peers and emotional empathy Scales to answer the research hypotheses; The research concluded to a set of results including the following: 1. The existence of a positive correlation between attachment to peers and emotional empathy in the research sample. 2. The existence of differences among master's students in degree of emotional empathy in favor of psychological disciplines. 3. An effect of the interaction between attachment to peers and emotional empathy in the research sample and it was a significant impact
لدى عينة من طلبة الماجستير في كلية التربية بجامعة دمشق
مقال
Keywords: التعلق بالأقران، التعاطف الوجداني; attachment to peers, emotional empathy.